Implementation of Stunting Prevention Program in East Bagan Sinembah, Rokan Hilir - Aisyah; Nst, Fitria Ramadhani Agusti (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Stunting is a growth and development disorder in children caused by chronic malnutrition and repeated infections due to the low quality of food consumed by children. This study aims to determine the implementation of the stunting prevention program in Bagan Sinembah Timur Village and to determine the inhibiting factors in the implementation of the stunting prevention program. This study uses a qualitative descriptive method, namely obtaining data from observations, interviews with related parties and documentation, then analyzed and described based on the actual situation. The results of the study indicate that the implementation of the stunting prevention program in Bagan Sinembah Timur Village has been running. The inhibiting factors in the implementation of stunting prevention are seen in economic factors, education factors, transportation factors, and communication factors